THE ANALYSIS OF NITRATE AND PHOSPHATE CONCENTRATION WITH DIATOM ABUNDANCE IN AIR HITAM STRAIT OF MERANTI ISLANDS REGENCY OF RIAU PROVINCE - Marpaung, Andre Thessalonians; Nurrachmi, Irvina; Ikhwan, Yusni (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The research was conducted in July 2014 in Air Hitam Strait of Meranti Islands Regency of Riau Province. This research aims to analyze the concentration of nitrate and phosphate and the relationship with diatom abundance. The samples were taken from 4 stations and each station was divided into 3 sampling points. The result showed the average value of nitrate and phosphate concentration were 0.122 mg/L and 0.021 mg/L. This research identified 12 genus of diatom. The highest abundance of diatom was found in Station 3 around of the floating cage locations (162.96 Ind/L) and the lowest was at Station 4 around harbor (111.11 Ind/L). The result of the simple linear regression of nitrate and phosphate concentration showed a positive relation with diatom abundance, that means if the concentration of nitrate and phosphate are raising the diatom abundance was also increasing.Keywords: Air Hitam Strait, Nitrate, Phosphate and Diatom